2020
DOI: 10.3390/ijerph17165672
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Obstacle Tracking to Natural Forest Resource Protection Project: A Rangers’ Case of Qilian Mountain, China

Abstract: Forests play an important role in the process of land degradation and restoration. As a national key ecological project for protecting natural forest, the natural forest resource protection project was implemented in 17 provinces for nearly 20 years. As the core stakeholders and main force for protecting forest resources, rangers have a clear, more objective and comprehensive perception of the policy process, problems and forest ecological changes than farmers. This study introduces public value theory, builds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Wang et al found that 28.6% of grassland restoration was attributed to grazing prohibition in the Qinghai–Tibet Plateau 4 . On the other hand, it may also be related to various ecological protection measures implemented by the government, such as protecting natural forests 76 , converting farmland to forests or grasslands 77 , and establishing the Qilian Mountain National Park Nature Reserve, which have had a positive influence on the vegetation 75 . Furthermore, considering the moderately degraded areas around Babao Town and Arou Township with point-distribution, this may be related to the overgrazing surrounding residential plots, resulting in a loss in vegetation cover 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that 28.6% of grassland restoration was attributed to grazing prohibition in the Qinghai–Tibet Plateau 4 . On the other hand, it may also be related to various ecological protection measures implemented by the government, such as protecting natural forests 76 , converting farmland to forests or grasslands 77 , and establishing the Qilian Mountain National Park Nature Reserve, which have had a positive influence on the vegetation 75 . Furthermore, considering the moderately degraded areas around Babao Town and Arou Township with point-distribution, this may be related to the overgrazing surrounding residential plots, resulting in a loss in vegetation cover 78 .…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid growth of the population and recreational demand in urban agglomeration areas, there may be a certain relationship between ecological restoration and recreational uses, but this impact has been overlooked compared to other perturbations [ 10 , 12 ]. The innovation of this study is to characterize the spatial distribution of ELR patterns, and to investigate the coupling mechanism of ELR and recreational use.…”
Section: Discussionmentioning
confidence: 99%
“…In many cities, the potential for human benefit (e.g., aesthetics, recreation) has become one of the driving forces for ELR [ 9 ]. In this context, an empirical examination of the spatial interaction between ELR and RUoEL in an urban agglomeration will provide insights into regionally environmental health planning to enhance the recreational well-being of residents [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of areas of difficult access is still a challenging task, even though novel advanced technologies have emerged, e.g., systems using infrared rays and cameras installed in fixed and mobile terrain locations [2]. Nowadays, the monitoring activity in these areas is still carried out in situ by one or several forest rangers located at fixed points within the territory and moving around when necessary [3], [4]. Since human personnel is required, these monitoring systems suffer from significant shortcomings as they (i) are unsuitable for situations that require real-time response since it is people who detect and report the hazard, (ii) compromise personnel safety by being close to the risk and (iii) could provide inaccurate information, leading to a misunderstanding of the magnitude of a hazard.…”
Section: Introductionmentioning
confidence: 99%